Pencucian Uang di Indonesia: Analisis dan Perspektif Islam - Nur Ayny Mufidah; Romi Faslah (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Money laundering is a serious problem that threatens economic stability and social order. This paper discusses money laundering in Indonesia from the perspective of positive law and Islam. Money laundering involves efforts to disguise the origin of illegal funds to make them appear legal. Based on positive law, money laundering is categorized as a criminal act regulated in Law No. 8 of 2010. From an Islamic perspective, money laundering is considered haram because it violates the principles of halal and transparency of transactions. Cases in Indonesia show the development of increasingly complex modus operandi with the use of technology. Therefore, a comprehensive legal approach and the application of Islamic values ​​are needed to prevent money laundering practices.